Acrylate resin and preparation method thereof, adhesive and preparation method thereof

By introducing acrylate resin with long carbon chain alkane structure into the adhesive and photothermal dual curing technology, the existing adhesives have been solved by using the main chain to introduce acrylate resin and photothermal dual curing technology in flexible display technology. The bonding performance of existing adhesives in high rigidity and high temperature and high humidity environments is reduced. Problem: High flexibility and high bond strength adhesives can maintain stable performance in extreme environments.

CN119431150AActive Publication Date: 2025-02-14HEFEI SINOPISE MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411576316.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

In flexible display technology, existing adhesives are not suitable for bending deformation of the substrate due to their high rigidity, resulting in peeling or damage, and their adhesive performance is degraded in high temperature and high humidity environments, making it difficult to prevent moisture from invading and causing corrosion of internal components.

Method used

Acrylate resin with a long carbon alkane structure is introduced by the main chain, and a tight three-dimensional network structure is formed through photothermal double curing, which improves the flexibility and bonding strength of the adhesive, and adds silane coupling agent and filler to enhance bonding. Stability and waterproofing.

Benefits of technology

Improve the elastic modulus and bonding strength of the adhesive, so that it can change with the change of curvature of the substrate, avoid cracking or failure, and maintain good bonding strength under high temperature and high humidity conditions, effectively blocking moisture penetration and protecting Internal components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431150A_ABST
    Figure CN119431150A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of resin synthesis, and particularly discloses acrylate resin and a preparation method thereof as well as an adhesive and a preparation method thereof. A long-carbon-chain alkane structure is introduced into a main chain of the acrylate resin provided by the invention, so that the movement capability of a molecular chain segment is enhanced, and the acrylate resin is endowed with relatively high flexibility and relatively low glass-transition temperature; therefore, the elastic modulus of the adhesive is improved, and the adhesive has higher bonding strength. Meanwhile, the acrylate resin is added into the adhesive, and through photo-thermal dual curing, acrylate groups can quickly react and crosslink to form a compact three-dimensional network structure. In addition, an alignment film in the liquid crystal display element is generally made of polyimide, the acrylate resin has a flexible framework, the similarity between the acrylate resin and a chain segment of the polyimide is high, the bonding force after curing is not prone to failure under the action of thermal expansion and cold contraction or mechanical stress, and the good bonding stability is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resin synthesis, and in particular relates to an acrylate resin and a preparation method thereof, an adhesive and a preparation method thereof. Background Art

[0002] In recent years, with the development of information technology and the growing demand for portable devices, display technology has continued to advance. Liquid crystal display elements (LCD) and organic electroluminescent display elements (OLED) have occupied an important position in the consumer electronics market due to their thinness, low power consumption and other characteristics. In the production process of liquid crystal display elements, in order to ensure the reliability and life of the display panel, adhesives made of curable resin compositions are usually used to seal the gap to prevent external contaminants from entering and affecting the display quality and service life. The adhesive is required to have not only good mechanical stability, but also to be able to maintain performance under various environmental conditions.

[0003] Traditional adhesives tend to be relatively rigid after curing, which is not a problem for glass substrates with small shape changes, but is no longer suitable for flexible display technology. When the substrate is bent and deformed, the highly rigid adhesive may peel off or break due to the inability to adapt to the deformation of the substrate. This is especially true for liquid crystal display components with narrow bezel designs, because the narrower the bezel, the less room there is for the adhesive. Not only does the adhesive need to form good adhesion with the surface of the substrate, but it also needs to maintain its bonding properties in extreme environments of high temperature and high humidity. At the same time, in order to ensure the long-term and reliable operation of the display device, the adhesive also needs to have excellent moisture resistance to prevent moisture intrusion that may cause corrosion or other damage to internal components. Summary of the invention

[0004] The object of the present invention is to overcome the above problems existing in the prior art and to provide an acrylate resin and a preparation method thereof, an adhesive and a preparation method thereof.

[0005] In order to achieve the above technical objectives, the present invention is implemented through the following technical solutions:

[0006] In a first aspect, the present invention provides an acrylate resin, the chemical structure of which is shown in formula (I):

[0007]

[0008] In the formula (I), X represents a hydrocarbon group having 1 to 20 carbon atoms.

[0009] In a second aspect, the present invention provides a method for preparing an acrylate resin, the method comprising the following steps:

[0010] S1. Dissolve dibromoalkane in tetrahydrofuran, add 1,3-dihydroxyacetone, triethylamine and potassium iodide, stir and react for 10-12 hours in a water bath at 60-70°C, adjust the pH to neutral after reaction, dry, filter and concentrate to obtain a crude product, and purify by silica gel column chromatography to obtain compound A;

[0011] S2, dissolving compound A and 4-[2-(4-chlorophenyl)propan-2-yl]benzoic acid in N,N-dimethylformamide, adding pyridine, stirring and reacting at 65-75° C. for 8-12 hours, post-reaction treatment, drying, filtering and concentrating to obtain a crude product, and purifying by silica gel column chromatography to obtain compound B;

[0012] S3, dissolving compound B in methanol, adding sodium borohydride, stirring and reacting at 0°C for 6-9h, adjusting the pH to 2, drying, filtering and concentrating to obtain a crude product, and purifying by silica gel column chromatography to obtain compound C;

[0013] S4. Compound C, 2-hydroxyethyl methacrylate and concentrated sulfuric acid are mixed, stirred evenly, and stirred at room temperature for 8-10 hours. After the reaction, the crude product is dried, filtered and concentrated, and purified by silica gel column chromatography to obtain an acrylate resin.

[0014] Further, in step S1, the dibromoalkane is any one of 1,8-dibromooctane, 1,9-dibromononane, 1,10-dibromodecane, 1,13-dibromotridecane, 1,15-dibromopentadecane, 1,16-dibromohexadecane, 1,17-dibromoheptadecane, 1,18-dibromooctadecane, 1,19-dibromononadecane, and 1,20-dibromoeicosane.

[0015] Furthermore, in step S1, the ratio of the amount of dibromoalkane, 1,3-dihydroxyacetone, triethylamine, potassium iodide and tetrahydrofuran is (21-31) g: (14.2-14.5) g: 9.7 g: (1.35-1.5) g: 200 mL.

[0016] Furthermore, in step S2, the ratio of compound A, 4-[2-(4-chlorophenyl)propan-2-yl]benzoic acid, pyridine and N,N-dimethylformamide is (22-30) g:(25-28) g:3 mg:270 mL.

[0017] Furthermore, in step S3, the ratio of compound B, sodium borohydride and methanol is (20-30) g:3.5 g:150 mL.

[0018] Furthermore, in step S4, the ratio of compound C, 2-hydroxyethyl methacrylate and concentrated sulfuric acid is (45-48) g: (3.1-3.2) g: 3 mg.

[0019] In a third aspect, the present invention provides an adhesive, comprising the following raw materials in parts by weight: 20-40 parts of acrylate resin, 40-60 parts of bisphenol A epoxy acrylate, 20-25 parts of bisphenol A epoxy resin, 1-5 parts of photo radical initiator, 1-5 parts of thermal radical initiator, 2-4 parts of hardener, 1-5 parts of silane coupling agent, and 25-32 parts of filler;

[0020] The acrylate resin is the acrylate resin provided in the embodiment of the first aspect of the present invention or the acrylate resin prepared by the preparation method of the acrylate resin provided in the embodiment of the second aspect of the present invention.

[0021] Further, the photo-radical initiator is any one or more of 2,2-dimethoxy-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholino)phenyl)-1-butanone, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, mixed in any proportion;

[0022] The thermal free radical initiator is any one or more of 4-cyanovaleric acid, 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide), and 2,2-azobisisobutyronitrile mixed in any proportion;

[0023] The hardener is any one or more of malonic acid dihydrazide, sebacic acid dihydrazide, isophthalic acid dihydrazide, and adipic acid dihydrazide mixed in any proportion;

[0024] The silane coupling agent is any one or more of 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, and 3-isocyanatepropyltrimethoxysilane mixed in any proportion;

[0025] The filler is any one or more of silicon dioxide, aluminum oxide, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, calcium silicate, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, and activated clay, mixed in any proportion.

[0026] In a fourth aspect, the present invention provides a method for preparing an adhesive, the method comprising the following steps: according to a formula, acrylate resin, bisphenol A epoxy acrylate, bisphenol A epoxy resin, photo radical initiator, thermal radical initiator, hardener, silane coupling agent, and filler are uniformly mixed, ground, and filtered to obtain an adhesive.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The main chain of the acrylic resin of the present invention introduces a long carbon chain alkane structure, which enhances the mobility of the molecular chain segments and gives the acrylic resin higher flexibility and lower glass transition temperature; thereby improving the elastic modulus of the adhesive, making it have higher bonding strength. At the same time, when the acrylic resin is added to the adhesive, after light and heat dual curing, the acrylate group will react and cross-link quickly to form a tight three-dimensional network structure. In addition, the material of the alignment film in the liquid crystal display element is usually polyimide. The acrylic resin of the present invention has a flexible skeleton and a high degree of similarity with the chain segments of polyimide. The bonding force after curing is not easy to fail under thermal expansion and contraction or mechanical stress, and has good bonding stability.

[0029] 2. The adhesive of the present invention has soft response performance. When applied to a flexible or semi-flexible display element, it can change with the curvature of the substrate and will not crack or fail due to bending or deformation of the substrate.

[0030] 3. The adhesive of the present invention has strong bonding properties to the oriented film and can establish a strong bond with the oriented film to ensure that there will be no display defects due to poor adhesion. It can also maintain its bonding strength under high temperature and high humidity conditions and effectively block moisture penetration to avoid damage to internal components. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0032] Figure 1 It is a curve diagram showing the change in adhesion of the adhesives provided in Examples 3-8 of the present invention and Comparative Examples 1-2 with displacement. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1 and Example 2 provide a method for preparing an acrylate resin M and a method for preparing an acrylate resin N, respectively.

[0035] Example 1

[0036] Embodiment 1 provides a method for preparing an acrylic resin M, comprising the following steps:

[0037] S1, dissolving 30.45 g of 1,20-dibromoeicosane in 200 mL of tetrahydrofuran, adding 14.28 g of 1,3-dihydroxyacetone, 9.7 g of triethylamine and 1.35 g of potassium iodide, stirring and reacting for 12 h in a 70° C. water bath, adjusting the pH to neutral after the reaction, drying, filtering and concentrating to obtain a crude product, and purifying by silica gel column chromatography to obtain compound A1;

[0038] S2, dissolving 28.94 g of compound A1 and 27.71 g of 4-[2-(4-chlorophenyl)propan-2-yl]benzoic acid in 270 mL of N,N-dimethylformamide, adding 3 mg of pyridine, stirring and reacting at 70° C. for 8 h, post-reaction treatment, drying, filtering and concentrating to obtain a crude product, and purifying by silica gel column chromatography to obtain compound B1;

[0039] S3, dissolving 25.23 g of compound B1 in 150 mL of methanol, adding 3.50 g of sodium borohydride, stirring and reacting at 0°C for 6 h, adjusting the pH to 2, drying, filtering and concentrating to obtain a crude product, and purifying by silica gel column chromatography to obtain compound C1;

[0040] S4, 47.56 g of compound C1, 3.19 g of 2-hydroxyethyl methacrylate, and 3 mg of concentrated sulfuric acid were mixed, stirred evenly, and stirred at room temperature for 8 h. After the reaction, the crude product was dried, filtered, and concentrated, and purified by silica gel column chromatography to obtain acrylate resin M;

[0041] The above preparation process is as follows:

[0042]

[0043] Example 2

[0044] Embodiment 2 provides a method for preparing acrylic resin N, comprising the following steps:

[0045] S1. Dissolve 24.5 g of 1,10-dibromodecane in 200 mL of tetrahydrofuran, add 14.28 g of 1,3-dihydroxyacetone, 9.7 g of triethylamine and 1.35 g of potassium iodide, stir and react for 10 h in a 60° C. water bath, adjust the pH to neutral after reaction, dry, filter and concentrate to obtain a crude product, purify by silica gel column chromatography to obtain compound A2;

[0046] S2, dissolving 22.47 g of compound A2 and 27.70 g of 4-[2-(4-chlorophenyl)propan-2-yl]benzoic acid in 270 mL of N,N-dimethylformamide, adding 3 mg of pyridine, stirring and reacting at 65° C. for 12 h, post-reaction treatment, drying, filtering and concentrating to obtain a crude product, and purifying by silica gel column chromatography to obtain compound B2;

[0047] S3, dissolving 20.15 g of compound B2 in 150 mL of methanol, adding 3.50 g of sodium borohydride, stirring and reacting at 0°C for 9 h, adjusting the pH to 2, drying, filtering and concentrating to obtain a crude product, and purifying by silica gel column chromatography to obtain compound C2;

[0048] S4, 45.05 g of compound C2, 3.19 g of 2-hydroxyethyl methacrylate, and 3 mg of concentrated sulfuric acid were mixed, stirred evenly, and stirred at room temperature for 10 h. After the reaction, the crude product was dried, filtered, and concentrated, and purified by silica gel column chromatography to obtain acrylate resin N;

[0049] The above preparation process is as follows:

[0050]

[0051] Examples 3-8 and Comparative Examples 1 and 2 provide an adhesive and a preparation method thereof.

[0052] Example 3

[0053] Example 3 provides an adhesive and a preparation method thereof, which are as follows:

[0054] An adhesive comprises the following raw materials in parts by weight: 20 parts of acrylate resin M, 60 parts of bisphenol A epoxy acrylate, 20 parts of bisphenol A epoxy resin, 1 part of photo radical initiator, 1 part of thermal radical initiator, 4 parts of hardener, 1 part of silane coupling agent, and 32 parts of filler;

[0055] Among them, the model of bisphenol A epoxy acrylate is EA-1010LC (Shin-Nakamura Chemical Industry Co., Ltd.); the model of bisphenol A epoxy resin is EXA-830CRP (DIC Corporation); the photo radical initiator is 2,2-dimethoxy-phenylacetophenone; the thermal radical initiator is 4-cyanovaleric acid; the hardener is malonic acid dihydrazide; the silane coupling agent is 3-glycidoxypropyltrimethoxysilane; the filler is silicon dioxide;

[0056] A method for preparing an adhesive comprises the following steps:

[0057] According to the formula, acrylate resin M, bisphenol A epoxy acrylate, bisphenol A epoxy resin, photo radical initiator, thermal radical initiator, hardener, silane coupling agent and filler are uniformly mixed, ground and filtered to obtain an adhesive.

[0058] Example 4

[0059] Example 4 provides an adhesive and a preparation method thereof, as follows:

[0060] An adhesive comprises the following raw materials in parts by weight: 30 parts of acrylate resin M, 50 parts of bisphenol A epoxy acrylate, 23 parts of bisphenol A epoxy resin, 2 parts of photo radical initiator, 3 parts of thermal radical initiator, 2 parts of hardener, 3 parts of silane coupling agent, and 28 parts of filler;

[0061] Among them, the model of bisphenol A epoxy acrylate is EA-1010LC (Shin-Nakamura Chemical Industry Co., Ltd.); the model of bisphenol A epoxy resin is EXA-830CRP (DIC Corporation); the photo radical initiator is 1-hydroxycyclohexyl phenyl ketone; the thermal radical initiator is 2,2-azobisisobutyronitrile; the hardener is sebacic acid dihydrazide; the silane coupling agent is 3-mercaptopropyltrimethoxysilane; the filler is montmorillonite;

[0062] A method for preparing an adhesive comprises the following steps:

[0063] According to the formula, acrylate resin M, bisphenol A epoxy acrylate, bisphenol A epoxy resin, photo radical initiator, thermal radical initiator, hardener, silane coupling agent and filler are uniformly mixed, ground and filtered to obtain an adhesive.

[0064] Example 5

[0065] Example 5 provides an adhesive and a preparation method thereof, as follows:

[0066] An adhesive comprises the following raw materials in parts by weight: 40 parts of acrylate resin M, 40 parts of bisphenol A epoxy acrylate, 25 parts of bisphenol A epoxy resin, 5 parts of photo radical initiator, 5 parts of thermal radical initiator, 3 parts of hardener, 5 parts of silane coupling agent, and 25 parts of filler;

[0067] Among them, the model of bisphenol A epoxy acrylate is EA-1010LC (Shin-Nakamura Chemical Industry Co., Ltd.); the model of bisphenol A epoxy resin is EXA-830CRP (DIC Corporation); the photo radical initiator is 2,2-dimethoxy-phenylacetophenone; the thermal radical initiator is 2,2'-azo (2-methyl-N-(2-hydroxyethyl) propionamide); the hardener is isophthalic acid dihydrazide; the silane coupling agent is 3-aminopropyltrimethoxysilane; the filler is alumina;

[0068] A method for preparing an adhesive comprises the following steps:

[0069] According to the formula, acrylate resin M, bisphenol A epoxy acrylate, bisphenol A epoxy resin, photo radical initiator, thermal radical initiator, hardener, silane coupling agent and filler are uniformly mixed, ground and filtered to obtain an adhesive.

[0070] Example 6

[0071] Example 6 provides an adhesive and a preparation method thereof, as follows:

[0072] An adhesive comprises the following raw materials in parts by weight: 20 parts of acrylate resin N, 60 parts of bisphenol A epoxy acrylate, 20 parts of bisphenol A epoxy resin, 1 part of photo radical initiator, 1 part of thermal radical initiator, 4 parts of hardener, 1 part of silane coupling agent, and 32 parts of filler;

[0073] Among them, the model of bisphenol A epoxy acrylate is EA-1010LC (Shin-Nakamura Chemical Industry Co., Ltd.); the model of bisphenol A epoxy resin is EXA-830CRP (DIC Corporation); the photo radical initiator is 2,2-dimethoxy-phenylacetophenone; the thermal radical initiator is 4-cyanovaleric acid; the hardener is malonic acid dihydrazide; the silane coupling agent is 3-glycidoxypropyltrimethoxysilane; the filler is silicon dioxide;

[0074] A method for preparing an adhesive comprises the following steps:

[0075] According to the formula, acrylate resin N, bisphenol A epoxy acrylate, bisphenol A epoxy resin, photo radical initiator, thermal radical initiator, hardener, silane coupling agent and filler are uniformly mixed, ground and filtered to obtain an adhesive.

[0076] Example 7

[0077] Example 7 provides an adhesive and a preparation method thereof, as follows:

[0078] An adhesive comprises the following raw materials in parts by weight: 30 parts of acrylate resin N, 50 parts of bisphenol A epoxy acrylate, 23 parts of bisphenol A epoxy resin, 2 parts of photo radical initiator, 3 parts of thermal radical initiator, 2 parts of hardener, 3 parts of silane coupling agent, and 28 parts of filler;

[0079] Among them, the model of bisphenol A epoxy acrylate is EA-1010LC (Shin-Nakamura Chemical Industry Co., Ltd.); the model of bisphenol A epoxy resin is EXA-830CRP (DIC Corporation); the photo radical initiator is 1-hydroxycyclohexyl phenyl ketone; the thermal radical initiator is 2,2-azobisisobutyronitrile; the hardener is sebacic acid dihydrazide; the silane coupling agent is 3-mercaptopropyltrimethoxysilane; the filler is montmorillonite;

[0080] A method for preparing an adhesive comprises the following steps:

[0081] According to the formula, acrylate resin N, bisphenol A epoxy acrylate, bisphenol A epoxy resin, photo radical initiator, thermal radical initiator, hardener, silane coupling agent and filler are uniformly mixed, ground and filtered to obtain an adhesive.

[0082] Example 8

[0083] Example 8 provides an adhesive and a preparation method thereof, as follows:

[0084] An adhesive comprises the following raw materials in parts by weight: 40 parts of acrylate resin N, 40 parts of bisphenol A epoxy acrylate, 25 parts of bisphenol A epoxy resin, 5 parts of photo radical initiator, 5 parts of thermal radical initiator, 3 parts of hardener, 5 parts of silane coupling agent, and 25 parts of filler;

[0085] Among them, the model of bisphenol A epoxy acrylate is EA-1010LC (Shin-Nakamura Chemical Industry Co., Ltd.); the model of bisphenol A epoxy resin is EXA-830CRP (DIC Corporation); the photo radical initiator is 2,2-dimethoxy-phenylacetophenone; the thermal radical initiator is 2,2'-azo (2-methyl-N-(2-hydroxyethyl) propionamide); the hardener is isophthalic acid dihydrazide; the silane coupling agent is 3-aminopropyltrimethoxysilane; the filler is alumina;

[0086] A method for preparing an adhesive comprises the following steps:

[0087] According to the formula, acrylate resin N, bisphenol A epoxy acrylate, bisphenol A epoxy resin, photo radical initiator, thermal radical initiator, hardener, silane coupling agent and filler are uniformly mixed, ground and filtered to obtain an adhesive.

[0088] Comparative Example 1

[0089] Comparative Example 1 provides an adhesive and a preparation method thereof, which are as follows:

[0090] An adhesive comprises the following raw materials in parts by weight: 20 parts of bisphenol A propylene glycol dimethacrylate, 60 parts of bisphenol A epoxy acrylate, 20 parts of bisphenol A epoxy resin, 1 part of photo free radical initiator, 1 part of thermal free radical initiator, 4 parts of hardener, 1 part of silane coupling agent, and 32 parts of filler;

[0091] Among them, the model of bisphenol A epoxy acrylate is EA-1010LC (Shin-Nakamura Chemical Industry Co., Ltd.); the model of bisphenol A epoxy resin is EXA-830CRP (DIC Corporation); the photo radical initiator is 2,2-dimethoxy-phenylacetophenone; the thermal radical initiator is 4-cyanovaleric acid; the hardener is malonic acid dihydrazide; the silane coupling agent is 3-glycidoxypropyltrimethoxysilane; the filler is silicon dioxide;

[0092] A method for preparing an adhesive comprises the following steps:

[0093] According to the formula, bisphenol A propylene glycol dimethacrylate, bisphenol A epoxy acrylate, bisphenol A epoxy resin, photo radical initiator, thermal radical initiator, hardener, silane coupling agent and filler are uniformly mixed, ground and filtered to obtain an adhesive.

[0094] Comparative Example 2

[0095] Comparative Example 2 provides an adhesive and a preparation method thereof, which are as follows:

[0096] An adhesive comprises the following raw materials in parts by weight: 20 parts of modified epoxy acrylate, 60 parts of bisphenol A epoxy acrylate, 20 parts of bisphenol A epoxy resin, 1 part of photo radical initiator, 1 part of thermal radical initiator, 4 parts of hardener, 1 part of silane coupling agent, and 32 parts of filler;

[0097] Among them, the model of modified epoxy acrylate is EBECRYL3708 (Zhenxin Company, USA); the model of bisphenol A epoxy acrylate is EA-1010LC (Shin-Nakamura Chemical Industry Co., Ltd.); the model of bisphenol A epoxy resin is EXA-830CRP (DIC Corporation); the photo radical initiator is 2,2-dimethoxy-phenylacetophenone; the thermal radical initiator is 4-cyanovaleric acid; the hardener is malonic acid dihydrazide; the silane coupling agent is 3-glycidoxypropyltrimethoxysilane; the filler is silicon dioxide;

[0098] A method for preparing an adhesive comprises the following steps:

[0099] According to the formula, modified epoxy acrylate, bisphenol A epoxy acrylate, bisphenol A epoxy resin, photo radical initiator, thermal radical initiator, hardener, silane coupling agent and filler are uniformly mixed, ground and filtered to obtain an adhesive.

[0100] Performance Testing

[0101] The performance of the adhesives prepared in Examples 3-8 and Comparative Examples 1-2 was tested, and the relevant test items and test procedures are as follows:

[0102] 1. Adhesion

[0103] The test was conducted using a universal material testing machine: (1) Sample preparation: Cut the glass into 4.5*2.5cm pieces, and use a glue dispenser (cross glue dispenser method) and a vacuum laminating machine (pressure: 0.5Pa, delay 5s) to prepare adhesion test samples, where the glass thickness is 0.5mm, the glue dispenser diameter is 3mm, and the glue dispenser thickness is 4μm; (2) UV (3000mj, 25cm) + heat (120℃, 50min) curing; (3) Test: Use a universal testing machine for adhesion test, with a pressure head diameter of 5mm and a push speed of 5mm / s; (4) Data processing: Use origin for data processing, and the results are shown in Tables 1 and 2. Figure 1 shown.

[0104] 2. Thixotropy

[0105] The viscometer was used for testing: (1) 4 g was taken and stored in a sample bottle at 25°C and 60% humidity; (2) 0.1 ml was taken for each test, with a No. 7 rotor and a rotation speed of 1 rpm / 5 rpm / 10 rpm; (3) Analysis of the results: Thixotropy (Ti value) was expressed as the ratio of 1 rpm to 10 rpm. The results are shown in Table 1.

[0106] 3. Adhesion after PCT

[0107] The PCT conditions are 121° C., 100% humidity, and 2 atmospheres. The test method for adhesion after PCT is consistent with the test method for adhesion. The results are shown in Table 1.

[0108] 4. Moisture permeability

[0109] (1) Prepare a 300 um thick adhesive film; (2) After UV (3000 mj, 25 cm) + heat (120°C, 50 min) curing, cut it into a ring shape that meets the requirements of the moisture permeability cup; (3) Under the conditions of temperature 85°C / humidity 85%, test the quality change of the film for 10 days. The results are shown in Table 1.

[0110] Table 1

[0111]

[0112] As shown in Table 1, the adhesives obtained in Examples 3-8 have better bonding properties than those in Comparative Examples 1 and 2, and can still maintain good bonding strength under high temperature and high humidity conditions, which fully demonstrates that the acrylic resin of the present invention can improve the bonding properties of the adhesive;

[0113] Specifically, compared with Example 1, in Comparative Examples 1 and 2, 20 parts of the acrylate resin M in the raw material composition of the adhesive are replaced with bisphenol A propylene glycol dimethacrylate and modified epoxy acrylate, respectively. From the test data of Example 3 and Comparative Examples 1 and 2 in Table 1, it can be seen that the acrylate resin provided by the present invention is added to the adhesive, and the prepared adhesive has better bonding performance.

[0114] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0115] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. An acrylate resin, characterized in that The chemical structure of the acrylic resin is shown in formula (I): In the formula (I), X represents a hydrocarbon group having 1 to 20 carbon atoms.

2. A method for preparing the acrylic resin according to claim 1, characterized in that: The method comprises the following steps: S1. Dissolve dibromoalkane in tetrahydrofuran, add 1,3-dihydroxyacetone, triethylamine and potassium iodide, stir and react for 10-12 hours in a water bath at 60-70°C, adjust the pH to neutral after reaction, dry, filter and concentrate to obtain a crude product, and purify by silica gel column chromatography to obtain compound A; S2, dissolving compound A and 4-[2-(4-chlorophenyl)propan-2-yl]benzoic acid in N,N-dimethylformamide, adding pyridine, stirring and reacting at 65-75° C. for 8-12 hours, post-reaction treatment, drying, filtering and concentrating to obtain a crude product, and purifying by silica gel column chromatography to obtain compound B; S3, dissolving compound B in methanol, adding sodium borohydride, stirring and reacting at 0°C for 6-9h, adjusting the pH to 2, drying, filtering and concentrating to obtain a crude product, and purifying by silica gel column chromatography to obtain compound C; S4. Compound C, 2-hydroxyethyl methacrylate and concentrated sulfuric acid are mixed, stirred evenly, and stirred at room temperature for 8-10 hours. After the reaction, the crude product is dried, filtered and concentrated, and purified by silica gel column chromatography to obtain an acrylate resin.

3. The method for preparing an acrylic resin according to claim 2, characterized in that: In the step S1, the dibromoalkane is any one of 1,8-dibromooctane, 1,9-dibromononane, 1,10-dibromodecane, 1,13-dibromotridecane, 1,15-dibromopentadecane, 1,16-dibromohexadecane, 1,17-dibromoheptadecane, 1,18-dibromooctadecane, 1,19-dibromononadecane, and 1,20-dibromoeicosane.

4. The method for preparing an acrylic resin according to claim 2, characterized in that: In the step S1, the ratio of the amount of dibromoalkane, 1,3-dihydroxyacetone, triethylamine, potassium iodide and tetrahydrofuran is (21-31) g: (14.2-14.5) g: 9.7 g: (1.35-1.5) g: 200 mL.

5. The method for preparing an acrylic resin according to claim 2, characterized in that: In step S2, the ratio of compound A, 4-[2-(4-chlorophenyl)propan-2-yl]benzoic acid, pyridine and N,N-dimethylformamide is (22-30) g: (25-28) g: 3 mg: 270 mL.

6. The method for preparing an acrylic resin according to claim 2, characterized in that: In step S3, the ratio of compound B, sodium borohydride and methanol is (20-30) g:3.5 g:150 mL.

7. The method for preparing an acrylic resin according to claim 2, characterized in that: In step S4, the ratio of compound C, 2-hydroxyethyl methacrylate and concentrated sulfuric acid is (45-48) g: (3.1-3.2) g: 3 mg.

8. An adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 20-40 parts of acrylate resin, 40-60 parts of bisphenol A epoxy acrylate, 20-25 parts of bisphenol A epoxy resin, 1-5 parts of photo radical initiator, 1-5 parts of thermal radical initiator, 2-4 parts of hardener, 1-5 parts of silane coupling agent and 25-32 parts of filler; The acrylate resin is the acrylate resin according to claim 1 or the acrylate resin prepared by the preparation method of the acrylate resin according to any one of claims 2 to 7.

9. An adhesive according to claim 8, characterized in that: The photo-free radical initiator is any one or more of 2,2-dimethoxy-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholino)phenyl)-1-butanone, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, mixed in any proportion; The thermal free radical initiator is any one or more of 4-cyanovaleric acid, 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide), and 2,2-azobisisobutyronitrile mixed in any proportion; The hardener is any one or more of malonic acid dihydrazide, sebacic acid dihydrazide, isophthalic acid dihydrazide, and adipic acid dihydrazide mixed in any proportion; The silane coupling agent is any one or more of 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, and 3-isocyanatepropyltrimethoxysilane mixed in any proportion; The filler is any one or more of silicon dioxide, aluminum oxide, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, calcium silicate, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, and activated clay, mixed in any proportion.

10. A method for preparing the adhesive according to any one of claims 8 to 9, characterized in that: The method comprises the following steps: according to the formula, acrylate resin, bisphenol A epoxy acrylate, bisphenol A epoxy resin, photo radical initiator, thermal radical initiator, hardener, silane coupling agent and filler are uniformly mixed, ground and filtered to obtain adhesive.

Citation Information

Patent Citations

  • Light-moisture dual-curing adhesive

    CN103232829A

  • Ultraviolet heated dual-cured adhesive for optical communication and preparation method thereof

    CN110358486A

  • UV-thermal dual-curing adhesive and preparation method thereof

    CN114702909A

  • Adhesive and UV adhesive tape

    CN115181515A

  • Fluorine-containing allyl compound, modified bismaleimide resin and preparation method and application of modified bismaleimide resin

    CN116253625A